A security routing protocol based on convergence degree and trust. (2017) - Chen, Ling; Qi, Xiaogang; Liu, Lifang; Zheng, Gengzhong
Wireless sensor networks are commonly used for critical security tasks such as intrusion or tamper detection, so they must be protected. Based on previous research, in this paper, we present a kind of routing protocol based on node convergence degree and the trust value which is named BCDTV. We focus on the security routing algorithm design and work process, including the election of cluster head and the establishment of cluster, the collection and transmission of the sensing information of wireless sensor networks. Simulation results show that the protocol can prevent some malicious behaviour of malicious nodes effectively.